2021
DOI: 10.3389/fnut.2021.726770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Selenium Sources on Physiological Status of Laying Hens and Production of Selenium-Enriched Eggs

Abstract: Developing new sources of organic selenium (Se) has potential benefits for animal production and human nutrition via animal-based foods enriched with Se. The objective of this study was to evaluate the effects of Se-enriched insect protein (SEIP) in comparison with other sources, such as sodium selenite (SS) and selenium-enriched yeast (SEY), on performance, egg quality, selenium concentration in eggs, serum biochemical indices, immune capacity, and intestinal morphology of laying hens. Four hundred and fifty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
(82 reference statements)
3
10
0
Order By: Relevance
“…Therefore, in this study, the performance improvement of laying hens benefits from the application of DCH, realizing the reuse of waste and reducing the production cost (Figure 3 ). Consistent with other studies, adding selenium to the layer diet can improve product performance and egg quality including yolk ratio, shell ratio, egg shape, shell thickness, yolk color, and so on ( 45 , 46 ), indicating that the DCH has the potential to use as a good feed additive to promote the growth and development of economic animals as well as improve economic benefits. This study of DCH provides an alternative strategy to improve egg quality and the development of novel feed additives.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, in this study, the performance improvement of laying hens benefits from the application of DCH, realizing the reuse of waste and reducing the production cost (Figure 3 ). Consistent with other studies, adding selenium to the layer diet can improve product performance and egg quality including yolk ratio, shell ratio, egg shape, shell thickness, yolk color, and so on ( 45 , 46 ), indicating that the DCH has the potential to use as a good feed additive to promote the growth and development of economic animals as well as improve economic benefits. This study of DCH provides an alternative strategy to improve egg quality and the development of novel feed additives.…”
Section: Discussionsupporting
confidence: 85%
“…Selenium revealed strong biological and nutritional influences in inducing physiology and production of poultry [6,7] that were primarily mediated by the activity of selenoproteins [55,93]. The dietary requirement of selenium for laying hens is comparatively low, at approximately 0.3 mg/kg [79]. Excess Se intake is toxic [101], and its inorganic form has limited biological availability, consequently its inclusion by high doses limits its utilization in poultry nutrition [120], as well as its emission to the environment is higher than the organic form [117].…”
Section: Selenium (Se)mentioning
confidence: 99%
“…Selenium is a trace element necessary for animal and human health. Selenium have been reported to enhance reproductive performance, antioxidant and immunomodulatory function in laying hens (144,145). In same vein, biofortification of eggs with selenium, evidenced by high content of selenium in albumen have been explored (145)(146)(147)(148)(149).…”
Section: Trace Elements and Vitaminsmentioning
confidence: 99%
“…Selenium have been reported to enhance reproductive performance, antioxidant and immunomodulatory function in laying hens (144,145). In same vein, biofortification of eggs with selenium, evidenced by high content of selenium in albumen have been explored (145)(146)(147)(148)(149). Other evidences showed that (Seenriched insect protein) (150) and selenium enriched yeast (148,151), enhanced albumen height and HU.…”
Section: Trace Elements and Vitaminsmentioning
confidence: 99%